Study of Adhesion Recovery phenomenon using a Multi-axle Roller-rig. Issue 1 (February 2021) - Magelli, Matteo
Abstract: When a railway vehicle is running on a contaminated track, the available friction is reduced, and large creep values arise at the wheel-rail interface. However, the work of the friction forces of the leading wheelsets produces a cleaning effect on both the track and the wheels, so that the contaminant layer is partially removed, and adhesion increases on the leading as well as on the trailing wheelsets. The investigation of these adhesion recovery phenomena is the key to develop new solutions aiming to improve the vehicle dynamic behaviour in degraded adhesion conditions. Since on-field tests are usually expensive and time-consuming, roller-rigs are the typical apparatus used to simulate the vehicle dynamic behaviour in laboratory conditions. The paper describes the mechanical design of an innovative roller rig specifically designed to study adhesion recovery phenomena, consisting of four wheelsets running over the same pair of rollers. Experimental tests are performed on the test bench to obtain adhesion characteristics under dry and contaminated conditions.